Direct Acquisition of the Gap Height of Biological Tissue‐Electronic Chemical Sensor Interfaces. Issue 43 (29th September 2022) - Zhang, Xin‐Wei; Hatamie, Amir; Ewing, Andrew G.
Abstract: Interfacing biological tissues with electronic sensors offers the exciting opportunity to accurately investigate multiple biological processes. Accurate signal collection and application are the foundation of these measurements, but a long‐term issue is the signal distortion resulting from the interface gap. The height of the gap is the key characteristic needed to evaluate or model the distortion, but it is difficult to measure. By integrating a pair of nanopores at the electronic sensor plane and measuring the ion conductance between them, we developed a versatile and straightforward strategy to realize the direct cooperative evaluation of the gap height during exocytotic release from adrenal gland tissues. The signaling distortion of this gap has been theoretically evaluated and shows almost no influence on the amperometric recording of exocytosis in a classic "semi‐artificial synapse" configuration. This strategy should benefit research concerning various bio/chemical/machine interfaces. Abstract : A pair of nanopores was integrated at the electrochemical sensor plane and used to measure the ion conductance between them providing a versatile strategy to directly determine the gap height during exocytotic release from tissues. Direct cooperative measurement of the gap height and exocytotic release at the same sensor can be used to address the long‐term question of the influence of diffusional filtering on the exocytotic spike.